Porosity and Permeability Development of the Deep-Water Late-Oligocene Carbonate Debris Reservoir in the Surroundings of the Paternoster Platform, South Makassar Basin, Indonesia - Gadjah E. Pireno; Emmy Suparka; Dardji Noeradi; Alit Ascaria (Institute for Research and Community Services, Institut Teknologi Bandung, 2015)
The discovery of gas within the carbonate debris reservoir of the late Oligocene Berai formation near the Paternoster Platform, South Makassar Basin, is a new exploration play in Indonesia. The carbonate was deposited in a deep-water environment and is a good example of a less well known carbonate play type. The carbonate debris reservoir in this area consists of re-deposited carbonate, originally located on a large carbonate platform that has been eroded, abraded and transported to the deep-water sub-basin. The limestone clasts range from pebble-size to boulders within a matrix of micrite and fine abraded bioclasts. This carbonate debris can be divided into clast-supported facies and matrix-supported facies. The matrix-supported facies have much better porosity and permeability than the clast-supported facies. Porosity in both the transported clasts and the matrix is generally mouldic and vuggy, resulting mostly from dissolution of foraminifera and other bioclastics after transportation. In the matrix intercrystal porosity has developed. The porosity and permeability development of this deep-water carbonate debris was controlled by a deep-burial diagenetic process contributed by the bathyal shales de-watering from the Lower Berai shales beneath the carbonate reservoir and the Lower Warukin shales above the carbonate reservoir during the burial process.